Weight gain responses of laying-type pullets to methionine plus cystine intake - Silva, E. P. [UNESP]; Lima, M. B. [UNESP]; Sakomura, N. K. [UNESP]; Moraes, L. E.; Peruzzi, N. J. [UNESP] (Cambridge Univ Press, 2020)
Each individual in the population has a distinct maximum growth potential, and the growth curve may vary depending on the response to nutrient intake, growth phase and variability among animals. The present study aimed to (1) model weight gain (WG) response to methionine+cystine (Met+Cys) supply using different mathematical functions, (2) identify functions that better fit the growth responses of pullets, (3) determine the Met+Cys requirements that maximize WG based on breeding standards and (4) partition the Met+Cys requirements for WG and maintenance. Three trials were performed using 1448 laying-type pullets. We adopted a completely randomized design with eight treatments and six replicates. The first trial (2 to 6 weeks, P1) used 15 pullets per experimental unit. The second and third trials (8 to 12 weeks, P2; 14 to 18 weeks, P3) were used eight pullets per replicate. The Met+Cys levels were obtained using a dilution technique. The mathematical functions used to describe WG responses to Met+Cys intake were broken line, broken line with curvilinear ascendancy, Michaelis-Menten, saturation kinetics and three logistic and three exponential models. Models were selected using the Bayesian information criterion and evaluated by residual analysis. It was possible to model the responses using the studied functions. The best functions were obtained by logistic and sigmoidal models in P1 and P2, and with the broken line by the curvilinear ascendancy model in P3. The Met+Cys intake that determined the maximum potential for WG (WG(max)) in P1, P2 and P3 were 313, 381 and 318 mg/day, respectively. The Met+Cys requirements for WG were 20, 22 and 27 mg/g, and for maintenance were 214, 53 and 30 mg/kgBW(0.75)for P1, P2 and P3, respectively.
Keywords: dilution technique; efficiency; maintenance; models; requirement